Community-based rehabilitation services implemented by multidisciplinary teams among adults with stroke: a scoping review with a focus on Chinese experience - Zifen An; Ke Li; Xinyi Yang; Jie Ke; Yuying Xu; Xi Zhang; Xianmei Meng; Xianwu Luo; Liping Yu (BMC, 2024)
Abstract Background Despite the growing interest in hospital rehabilitation services for communities, studies on existing community-based rehabilitation (CBR) services remain scarce owing to limitations in the development of community health services and regional cultural diversity. As a guaranteed measure for ensuring the quality of rehabilitation services and achieving the desired service outcomes, clear roles and responsibilities in multidisciplinary teams and effective service delivery are particularly important. Objective This scoping review aimed to determine the scope of community stroke rehabilitation programs involving existing multidisciplinary teams and to analyze the implementation content and implementers' functional roles to provide guidance for future CBR programs. Methods The scoping review design followed the methodology of the Joanna Briggs Institute and was based on the normative scoping review framework proposed by Arksey and O'Malley. The comprehensive CBR framework was proposed by World Health Organization-guided data charting and analysis. Results Of the 22,849 identified citations, 74 studies were included, consisting of 6,809 patients with stroke and 49 primary caregivers, most of whom were from China. The most common working mode in CBR programs was a dual approach involving both healthcare professionals in medical institutions and community healthcare professionals. The number of programs in each discipline was in the following descending order: nursing, medical care, rehabilitation, psychology, nutrition, and public health. Among these, multidisciplinary teams comprising medical, nursing, and rehabilitation disciplines were the most common, with a total of 29 programs. Disciplinary members were mainly responsible for implementing their respective disciplinary content, with physicians providing guidance for the programs. More than 82.4% of the studies reported 2-4 intervention strategies. The intervention forms of rehabilitation content were the most diverse, whereas preventive interventions were more homogeneous than others. Physical function and socio-psychological measurements were the most commonly reported outcomes. Conclusion CBR services implemented by multidisciplinary teams can effectively achieve functional and emotional improvement in patients with stroke, and nurses are the most involved in implementation, especially in community settings. The results further emphasize the importance of strengthening the exploration of nurses' maximum potential to implement CBR plans in future practice. Trial registration The registration information for this scoping review can be found at osf.io/pv7tg.